Becoming other: literary multilingualism in the Chinese badlands. Issue 2 (1st February 2020) - Sim, Wai-chew
ABSTRACT: My essay concerns two Singapore novels: an 'English' text that switches at a key moment into Chinese (Vyvyane Loh's Breaking the Tongue ) (USA, 2004), and a 'Chinese' text that does the opposite (Joo Ming Chia's Exile or Pursuit ) (Singapore, 2015). Discussing the local and translocal significance of such experimentation, I suggest that the pursuit of bilingual/multilingual aesthetics in these works resists the linguistic monism that fosters restrictive identitarianisms in both the 'Anglo' and the 'Chinese' cultural domains. They gesture at an ongoing 'Anglo-Chinese' cultural syncretism pertinent to Singapore and Malaysia, Hong Kong and Macau, and also other parts of the world. Because both works also affirm the mestizaje between regional Chinese and autochthonous Southeast Asian culture/s, I argue that they present new models for approaching Sinitic literary and cultural studies, and also for Southeast Asian studies more generally. Instead of the stagnant East–West master narrative, which is susceptible to populist and authoritarian manipulation in both East and West, the suggested approach orients discussion towards issues of 'South-South' (or East-Southeast Asian) cultural exchange and dialogue. This shift uncovers what I call 'Badlands' writing, which acts to undermine discourses of Chinese essentialism and exceptionalism.